(untitled) (Journal of Nonlinear Modeling and Analysis, 2025)
By applying the Mountain Pass Theorem, we establish the existence of a weak solution for a class of nonlinear elliptic problem involving an α(z)-biharmonic operator and with an l(z)-hardy term in a bounded domain of R^N. Provided that certain additional assumptions are made regarding the nonlinearities, the corresponding functional will satisfy the Palais-Smale condition.